Annotation of Hans Bethe’s paper, Zeitschrift fur Physik 76, 293 (1932), “Braking Formula for Electrons of Relativistic Speed” - Fontes, C.; Bostock, Christopher; Bartschat, K. (Springer, 2014)
We present an annotation of Hans Bethe’s “Bremsformel für Elektronen relativistischer Geschwindigkeit” [Zeitschrift für Physik 76, 293 (1932)] (Braking Formula for Electrons of Relativistic Speed). The English translation of the paper appears as a companion to this annotation. We highlight the conceptual and historical aspects of the relevant quantum electrodynamics employed by Bethe, provide details in the derivation of several equations, and point out some typographical errors in the original manuscript.